Detection of Ralstonia solanacearum in Solanum tuberosum L. in Sonora, Mexico - Alvarado-Martínez, Ana G.; Rueda-Puente, Edgar O.; Ponce-Medina, Juan F.; Avendaño-Reyes, Leonel; Santillano-Cazares, Jesús; Borboa-Flores, Jesús; Hernández-Montiel, Luis; Holguín-Peña, Ramón (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
Ralstonia solanacearum (Rs) causes the disease quarantine called bacterial wilt in potatoes. Mexico importseed from United States of America (USA) and Canada, which is a significant aspect to eventual introduction of the disease in areas with large tracts of potato. Sonora is an important region in relation to potato production. Therefore, this research was conducted, with the following objectives: a) production of antibody for Rs; b) diagnosis of Rs in foreign tuber, and in tuber for human consumption which is used for seed; c) detection of Rs in vegetative growth of potato lots in Sonora, Mexico. We analyzed seed, seedling, leaf and tuber; the detection methods used were: specific means, ELISA, antiserum produced and pathogenicity tests. The positive results have shown the presence of Rs in tubers for consumption; in foreign tuber and vegetative stages it was negative. The separate testing should not be used as a unique method of detection; the presence of Rs, represents a risk of eventual manifestation of the disease, so it is necessary to undertake activities with preventive phytosanitary control.